2013
DOI: 10.5194/bgd-10-2857-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CellTracker Green labelling vs. Rose Bengal staining: CTG wins by points in distinguishing living from dead anoxia-impacted copepods and nematodes

Abstract: Hypoxia and anoxia have become a key threat to shallow coastal seas. Much is known about their impact on macrofauna, less on meiofauna. In an attempt to shed more light on the latter group, in particular from a process-oriented view, we experimentally induced short-term anoxia (1 week) in the Northern Adriatic Sea, Mediterranean, and examined the two most abundant meiofauna taxa – harpacticoid copepods and nematodes. Both taxa also represent different ends of the tolerance spectrum, with copepods being the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Moreover, novel approaches, such as the use of vital stains, may allow a more accurate assessment of alive/dead individuals following short-term impact by hypoxia and anoxia (e.g. see Grego et al, 2013a, for copepods and nematodes). Harpacticoid copepods were the most sensitive meiofauna taxa to low oxygen concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, novel approaches, such as the use of vital stains, may allow a more accurate assessment of alive/dead individuals following short-term impact by hypoxia and anoxia (e.g. see Grego et al, 2013a, for copepods and nematodes). Harpacticoid copepods were the most sensitive meiofauna taxa to low oxygen concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As there was no significant difference in overall density between the natural (normoxic) and the treated cores (anoxia), we conclude that the impacted meiofauna community corresponded to a "natural, pristine" meiofauna community. Note that the meiofauna counts for this study were based on rose-bengalcoloured individuals and may therefore be an overestimation of the actual number of life animals (see Grego et al, 2013a).…”
Section: In Situ Experimentsmentioning
confidence: 99%
“…Harpacticoid copepods are the most sensitive meiofauna taxa to low oxygen concentrations . Several studies have shown that nematodes are generally more resistant to hypoxia than copepods (Murrell and Fleeger 1989;Modig and Olafsson 1998;Grego et al 2013;Sergeeva and Zaika 2013). Copepods may stop feeding under anoxic conditions, yielding increased primary producer levels .…”
Section: Response To Ocean Deoxygenationmentioning
confidence: 99%
“…Several studies showed that nematodes are generally more resistant to hypoxia than copepods (Murrell and Fleeger 1989;Modig and Olafsson 1998;Grego et al 2013;Sergeeva and Zaika 2013). Nematodes are adapted to these extreme conditions (e.g.…”
Section: Adaptation Of Meiofauna To Hypoxia and Anoxiamentioning
confidence: 99%